Student perceptions and community orchards family income as a strategy for learning and university-community involvement (Agroindustria, Sociedad y Ambiente, 2016)
The university must play a key role in the transformation of knowledge and social changes, by linking university and society. To that end, our objective was to establish the perception of students and community on the establishment of home gardens as a bonding experience university and community. Involved 28 students studying the curriculum unit Olericulture Fruticulture and Agricultural Technology Program in the academic period 2008-I, organized into five groups (one per family) to support the establishment of home gardens in the community Chirico, Torres municipality, Lara state. 5 families with available land and water were selected and given near coop, seeds and support students in preparing the soil, planting and crop. Home gardens were established with the use of organic fertilizer and planting vegetables short cycle. Subsequently, a questionnaire for students studying on the review of learning in planting and crop management olerícolas and interview community members was performed. It was found that 78% of students felt that the strategy of establishing home gardens in the El Chirico community knowledge and skills acquired in soil preparation, composting, planting identification of various types of vegetables. It is concluded that the establishment of home gardens allowed linking the University and the community.